Ecokinetics of herbicides from farmland to the river : a case study of Chanthaburi Estuary in Thailand - Kitiya Totong; Jutamaad Satayavivad; Preeda Pakpian; Napaporn Leadprathom; Nuchanart Rangkadilok; Wattanaporn Meskultavon; S & T Postgraduate Education and Research Development Office (PERDO), Ministry of Education, Thailand; RTG fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Ecokinetics of herbicides such as paraquat and glyphosate from farmland to Chanthaburi River and its estuary, Thailand were investigated by using hot spots identified. At the same time, the field trial with planting vetiver grass strips was conducted to observe runoff catchment and to retard agrochemical contamination to river. This study aims to understand transportation, transformation, distribution, and accumulation of these herbicides which runoff from agricultural areas into Chanthaburi River and its estuary. Paraquat and glyphosate residues in environmental medias; soil, water, suspended solid (SS), and sediment were analyzed by spectrophotometric method and HPLC method, respectively. Field trial with planting vetiver grass strips and the non-planted plots to study on runoff catchment and reduce herbicide contamination was limited due to fluctuation of weather. However, paraquat residues in soil upper plots at the end of rainy season were higher than at the initial month that had no rainfall. In addition, paraquat and glyphosate residues in water, SS, and sediment samples in the collecting tanks of the planted and non-planted plots were found. These could indicate that the increasing of herbicides in soil of upper plots at the end of rainy season was due to runoff and washing eroded soil and particles from farmland which is a source of agrochemical using areas around the field trial. At the end of rainy season, paraquat and glyphosate concentrations in water samples from the collecting tanks were higher than in dry season and glyphosate residues were found to have higher concentration than paraquat residues. In contrast, paraquat and glyphosate concentrations in SS and sediment samples from the collecting tanks in dry season were found to have higher than at the end of rainy season but glyphosate residues in SS and sediment samples were less concentration than paraquat residues. While planting vetiver grass strips as a mitigation measure to reduce contamination and transportation of agrochemicals to the river was interested and applied by the farmers and local people in communities surrounding the field trial. Field survey with four hot spots and one reference point along Chanthaburi River and its estuary was focused with various activities including taking water, SS, and sediment samples at two times (in rainy and dry seasons) to determine transportation, transformation, distribution, and accumulation of paraquat and glyphosate contamination. The results showed that paraquat residues in water and SS samples from Chanthaburi River in rainy season were higher than in dry season and the highest paraquat concentrations in water samples in rainy season were found at the station 2 and 3 which are representatives for agrochemical usage areas, at the concentrations of 1.51 and 1.21 o g/L (ppb), respectively. The highest paraquat concentration in SS sample of rainy season was also found at the station 2 with concentration of 9.68 mg/kg dry weight. In surface layer of sediment (0-5 cm.) in two seasons, the high paraquat concentrations were found at agrochemical usage areas and aquatic area in the range of 0.38-0.56 mg/kg dry weight. Particularly, in dry season, Chanthaburi estuary was found to have the highest paraquat concentration in sediment samples both at the surface layer (0-5 cm.) and deeper layer (5-10 cm.) at the concentration of 0.56 and 0.66 mg/kg dry weight, respectively. Furthermore, the high glyphosate concentrations in water and sediment samples from hot spots in rainy season were also found at the aquatic area with concentration of 3.46 og/L and 0.45 og/g wet weight, respectively. These results could implicate transportation, transformation, distribution and accumulation including the horizontal and vertical movements of herbicides in Chanthaburi River water, SS, and sediment. However, Chanthaburi River and its estuary area were considered to safe for aquatic ecosystem.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management Inter-University Program on Environmental Toxicology, Technology and Management
Thesis (M.Sc.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2010
Keywords: Herbicides -- Toxicology -- Chanthaburi River (Thailand); Glyphosate -- Chanthaburi River (Thailand); Paraquat -- Chanthaburi River (Thailand)